2009
DOI: 10.1295/polymj.pj2008324
|View full text |Cite
|
Sign up to set email alerts
|

Development of Liquid-Crystalline Semiconductors with High Carrier Mobilities and Their Application to Thin-film Transistors

Abstract: Carrier transport in liquid-crystal phases, design of liquid-crystalline semiconductors with high carrier mobilities, and their application to field-effect transistors are reviewed. High carrier mobility has been observed in the smectic phases of oligothiophene derivatives as well as in the columnar phases of triphenylene and hexabenzocoronene derivatives. The mobility increases with the molecular ordering in the mesophases and extension of the -conjugated system of the liquidcrystal molecules. Asymmetrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(58 citation statements)
references
References 79 publications
0
58
0
Order By: Relevance
“…For example, the DSC thermogram of C 6 -DNF-VW shows several small endothermic peaks ranging from 150 to 220°C and a large endothermic peak at 246°C (Figure 4d), which corresponds to a crystalline-smectic phase-transition and a subsequent smectic-isotropic liquid phase-transition. 19 During a cooling process from the isotropic liquid phase at a rate of 1 K min -1 , these two transition peaks were detected separately, suggesting the formation of the smectic phase from 243.5 to 241.6°C (Supplementary Figure 4). Indeed, from observations of samples under a polarized optical microscope, the typical focal conic texture of the smectic phases was observed in this narrow temperature range (Supplementary Figure 5).…”
Section: Thermal Propertiesmentioning
confidence: 98%
“…For example, the DSC thermogram of C 6 -DNF-VW shows several small endothermic peaks ranging from 150 to 220°C and a large endothermic peak at 246°C (Figure 4d), which corresponds to a crystalline-smectic phase-transition and a subsequent smectic-isotropic liquid phase-transition. 19 During a cooling process from the isotropic liquid phase at a rate of 1 K min -1 , these two transition peaks were detected separately, suggesting the formation of the smectic phase from 243.5 to 241.6°C (Supplementary Figure 4). Indeed, from observations of samples under a polarized optical microscope, the typical focal conic texture of the smectic phases was observed in this narrow temperature range (Supplementary Figure 5).…”
Section: Thermal Propertiesmentioning
confidence: 98%
“…Hexabezocoronene (HBC) is a well-known discotic liquid crystal which self-organizes to form columns with strong π-orbital interactions between molecules within columns. Such materials, often referred to as an alternative to thin films of organic semiconductors, possess many characteristics that are important in solar cells (Funahashi, 2009): improved vertical mobility, self-annealing and self-assembling characteristics that give rise to larger domains thus reducing charge-trapping sites. Time-resolved microwave conductivity (TRMC) measurements have shown that hole mobility in HBC is well above 0.1 cm 2 V −1 s −1 and depends on side chains (van de Craats et al, 1999).…”
Section: Some Other Materials Used In Opvsmentioning
confidence: 99%
“…al. (Vukmirović & Wang, 2008;2009) have developed a multi-scale ab initio method of simulating charge-carrier transport that provides a systematic means of combining density functional calculations of small-scale local structural motifs to obtain the electronic structure and charge-transport properties of organic semiconductors up to the 100 nm length scale. But this method has only been applied to studying pure materials so far.…”
Section: Kinetic Monte Carlo Modelsmentioning
confidence: 99%
“…Liquid-crystalline (LC) semiconductors, including columnar, smectic and nematic compounds, have been studied by European and Japanese researchers. [2][3][4][5] In the LC phases, electronic charge carriers are transported by the hopping mechanism, although band-like conduction has been reported in ordered smectic phases. 6,7 In addition to basic research, the application of these materials to electronic devices, such as light emitting diodes, 8 field-effect transistors 9 and solar cells, 10,11 has been studied.…”
Section: Introductionmentioning
confidence: 99%